AJSCCR 2021
DOI: 10.47829/ajsccr.2021.2701
|View full text |Cite
|
Sign up to set email alerts
|

A Predictive Factor For Short-Term Outcome In Patients With COVID-19: CT Score For Lung Involvement

et al.

Abstract: 1.1. Background: Recently, typical CT features of coronavirus disease (COVID-19) pneumonia have been reported. However, the prognostic value of CT evaluations has not been fully elucidated. Methods:In this retrospective, multi-center cohort study, we reviewed 645 patients who had died or recovered from laboratory-confirmed COVID-19 between January 23, 2020 and March 6, 2020 in two hospitals in Wuhan and Shenyang, China. Demographic, clinical, laboratory, and CT data were extracted and compared between the non-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 27 publications
1
2
0
Order By: Relevance
“…Researches have shown that the microbes in oligotrophic lakes on the northern Qinghai-Tibet Plateau are dominated by Actinobacteria and Verrucomicrobia (Liu et al, 2019;Gu et al, 2021), which was consistent with the results of this study using selected lakes on the Qinghai Tibet Plateau. The microbial composition of Erhai, Fuxian Lake, Bohu Lake, and Daye Lake also corroborates previous literature records (Hong et al, 2011;Bai et al, 2020).…”
Section: Discusssion Lake Microbial Community Diversity Response To E...supporting
confidence: 92%
See 1 more Smart Citation
“…Researches have shown that the microbes in oligotrophic lakes on the northern Qinghai-Tibet Plateau are dominated by Actinobacteria and Verrucomicrobia (Liu et al, 2019;Gu et al, 2021), which was consistent with the results of this study using selected lakes on the Qinghai Tibet Plateau. The microbial composition of Erhai, Fuxian Lake, Bohu Lake, and Daye Lake also corroborates previous literature records (Hong et al, 2011;Bai et al, 2020).…”
Section: Discusssion Lake Microbial Community Diversity Response To E...supporting
confidence: 92%
“…Lakes with different terrain ladders (terrains of contrasting elevation levels) have special living environments and abundant microbial taxa, which play diverse roles in energy metabolism and material circulation (Eiler et al, 2012;Xing et al, 2020;Tran et al, 2021). Many studies have shown that different microbial communities can complement each other in the biogeochemical cycle (Rathour et al, 2020;Liu et al, 2021). However, there are few studies on the lateral comparison of the microbial community structure among lakes in different ladders and their roles in biogeochemical cycles using functional metagenomics.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that a high-energy intermediate, DOD, formed by the CPPO−H 2 O 2 CL system, readily transfers its energy to a neighboring fluorophore, like BSA@AuNCs. 19,31,32 Therefore, CL resonance energy transfer can occur from the high-energy intermediate DOD, generated by the oxidation of CPPO with H 2 O 2 , to BSA@AuNCs. In brief, the CL emission of CPPO/BSA@AuNCs is initiated by H 2 O 2 , which decomposes CPPO to form a high-energy DOD that subsequently induces NIR CL emission.…”
Section: Mechanism Of the Nir CL Nanoprobesmentioning
confidence: 99%
“…The San Jacinto River flows through two lake basins to merge with the Santa Ana River 68 km downstream from its source. However, its flow is only rarely sufficient to fill either basin, the San Jacinto (Wang et al, 1995) or Lake Elsinore (3 times since 1900 and 20 times since 1769, Kirby et al, 2007), and reach the Santa Ana River and, thereby, the ocean. This combination suggests a relatively recent integration of the San Jacinto River through its length (68 km).…”
Section: Amargosa Rivermentioning
confidence: 99%